Severe myocardial injury and extracorporeal membrane oxygenation following perinatal asphyxia - P. Benson Ham; Pinkal Patel; Linda J. Wise; Christian Walters; Brian K. Stansfield (Elsevier, 2015)
Perinatal asphyxia is a common cause of morbidity and mortality in the newborn and is associated with myocardial injury in a significant proportion of cases. Biomarkers, echocardiography, and rhythm disturbances are sensitive indicators of myocardial ischemia and may predict mortality. We present a case of severe myocardial dysfunction immediately after delivery managed with extracorporeal membrane oxygenation (ECMO) and discuss the role of cardiac biomarkers, echocardiography, electrocardiography, and ECMO in the asphyxiated newborn.